Work related thumb pain, its prevalence, risk factors and prevention among physical therapists - Yaseen, Areesa; Yaseen, Hajra; Yaseen, Amna (International Journal of Endorsing Health Science Research, 2019)
Background: Previous studies conducted worldwide which indicated that many physical therapists are prone to develop a thumb pain just because of their occupation. The nature of the work in a physical therapy practice is physically demanding which prone the physiotherapists to work related thumb pain (WRTP) as it involves repetitive tasks, high force manual techniques for treating patients. The objective of this study was to investigate the prevalence, risk factors and consequences of thumb pain arising due to physiotherapy. Methodology: An observational cross-sectional study was conducted from December 2017 to December 2018 and participating population included both male and female physiotherapists who are currently in practice. Participants that have undergone forearm or hand surgery, victim of rheumatoid arthritis (RA) and those who were retired or working out of Karachi were excluded. The sample size was calculated through open epi version 3.0 and data was collected from 100 subjects from districts of Karachi (Saddar, Liaquatabad, North Karachi, Gulberg, North Nazimabad, Malir, Gulshan, Korangi and Orangi). The data was analyzed using SPSS Version 22. Pearson’s Chi square test was used to find out the association between WRTP among physical therapists. Results: According to the study results physical therapists are at increased risk of developing WRTP, with prevalence of 48%. Physiotherapists that are most commonly affected by WRTP are 39% and they aged <30 years. It was found more prevalent among manual therapists (29%). Trigger point therapy is mentioned by 23% of the respondents as an important pain exacerbating cause for their WRTP. Also, manipulation (17%) and mobilization (17%) are the techniques that result in thumb pain. Change in the choice of treatment techniques (17%) is a consequence of WRTP. Conclusion: Physical therapists who are using manual therapy techniques in musculoskeletal conditions experienced more WRTP. However, thumb pain is mostly provoked by trigger point therapy. The best therapy for WRTP is rest, considering the most satisfaction about this treatment.